Opsonic Activity of Normal Human Cerebrospinal Fluid for Selected Bacterial Species - Tofte, Robert W. (1979)
The opsonic activity of normal human cerebrospinal fluid (CSF) has not been well defined. In this study, the opsonic activity of normal CSF for laboratory and blood culture isolates of Staphylococcus aureus, Streptococcus pneumoniae, Escherichia coli, Hemophilus influenzae type b, and Neisseria meningitidis was measured by a quantitative assay employing radiolabeled bacteria and polymorphonuclear leukocytes. All isolates of S. aureus, except the Wood 46 strain, were opsonized in undiluted CSF (>50% uptake by polymorphonuclear leukocytes.) There was heat-stable and heat-labile opsonic activity in CSF for S. aureus. Only one blood culture isolate of E. coli was moderately well opsonized in undiluted CSF (26% uptake). None of the remaining laboratory or clinical isolates were opsonized in undiluted CSF. The S. aureus isolates were more readily opsonized in dilute normal serum than were the other bacterial species, and complement appeared to be the heat-labile opsonin in serum. However, complement may not be the heat-labile opsonin in normal CSF for S. aureus. In contrast to serum, complement C3 was not visualized on the staphylococcal cell surface by immunofluorescence microscopy and chelation of CSF did not diminish opsonic activity. This study demonstrates that normal CSF is opsonic for S. aureus but not for bacterial species that more commonly cause meningitis. These species differences in opsonic requirements may be important in the pathogenesis of meningitis.